Weightlifting and the knee - Urso, A.; Voglino, N. (EWF Scientific Magazine, 2015)
The knee joint can certainly be considered among the most stressed joints in sports alongside the elbow and shoulder. In particular, it has been observed that when practising Olympic weightlifting, the knee is subjected to repeated flexion-extension movements with heavy loads, undoubtedly producing functional stress, as occurs in other sports, where technical skills require repetitive, sudden and ballistic movements of the knee: football, handball, tennis, volleyball, basketball, jumps (long, triple and high), fencing, cycling, skiing and gymnastics. The menisci play a key role in the congruence between the femoral and tibial articular surface. Any alteration, however small, of the structure of the meniscal fibrocartilage tissue leads to a higher load transmission on the tibial cartilage and subchondral bone. For this reason, the aim of arthroscopic meniscus surgery should be to save as much meniscal tissue as possible.